The Pedagogy of Intimacy: Mother's Contribution to Academic Parenting during Student's Learning from Home - Mutiara Andalas (Salasika, 2020)
This essay strives to articulate the pedagogy of intimacy born from mothers' engagement in academic parenting when formal learning shifts from school to home. Redefining parenting and intimacy, mothers implicitly articulated an alternative pedagogy when the space and time of learning during the Covid-19 pandemic move to home. Listening to the self-narratives of mothers who work full time at home, at least part-time, as informants in thisqualitative study, the words "parenting" and "intimacy" were prominent inthe semi-structured interviews. In the pre-pandemic seasons, these wordswere identical to activities at home and were seen as unrelated, at leastlimitedly related, to formal education. Learning from home, especially withmothers' engagement in informal learning during the Covid-19 pandemic,challenges the boundaries of maternal involvement in the formal educationspace. Mothers re-centralize home both as space and as a time for learning.Mothers reiterate their central role as informal teachers, further pedagogues,in children's education. Articulating intimacy's pedagogy, they reclaim homeboth as the steaming time and ubiquitous space for self-determined learning.